Evidence-based Anticancer Materia Medica - Cho, William C.S.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
Cancer is one of the leading killers in the world and the incidence is increasing, but most cancer patients and cancer survivors suffer much from the disease and its conventional treatments$1 (Bside effects. In the past, clinical data showed that some complementary and alternative medicine (CAM) possessed anticancer abilities, but some clinicians and scientists have queried about the scientific validity of CAM due to the lack of scientific evidence. There is great demand in the knowledge gap to explore the scientific and evidence-based knowledge of CAM in the anticancer field. With this aim, a book series is needed to structurally deliver the knowledge to readers. Recently there have been encouraging results from both laboratory experiments and clinical trials demonstrating the anticancer effects of herbal medicine. There is considerable interest among oncologists and cancer researchers to find anticancer agents in herbal medicine. This volume is a specialised book presenting the up-to-date scientific evidence for anticancer herbal medicine. This unique book provides an overview of the anticancer herbal medicines and remedies, as well as a detailed evidence-based evaluation of 18 common anticancer herbal medicines covering their biological and pharmacological properties, efficacies, herb-drug interactions, adverse effects, pre-clinical studies, and clinical applications. Gathering international opinion leaders$1 (Bviews, this volume will contribute great to the cancer, academic, and clinical community by providing evidence-based information on the anticancer efficacy of herbal medicine. Readership Oncologists, cancer researchers, pharmacologists, pharmaceutical specialists, Chinese medicine practitioners, medical educators, postgraduates and advanced undergraduates in biomedical disciplines, cancer caregivers, cancer patients.s
Preface -- 1.An Overview of Anticancer Herbal Medicines -- 2.An Evidence-based Perspective of Arsenic Trioxide (As2O3) for Cancer Patients -- 3.An Evidence-based Review of Astragalus Membranaceus (Astragalus) for Cancer Patients -- 4.An Evidence-based Perspective of Panax Ginseng (Asian Ginseng) and Panax Quinquefolius (American Ginseng) as a Preventing or Supplementary Therapy for Cancer Patients -- 5.Panax Quinquefolius (American Ginseng) and Panax Notoginseng (Notoginseng) in Cancer Chemoprevention -- 6.An Evidence-based Perspective of Coptis Chinensis (Chinese Goldthread) for Cancer Patients -- 7.An Evidence-based Perspective of Angelica Sinensis (Chinese Angelica) for Cancer Patients -- 8.An Evidence-based Perspective of Scutellaria Barbata (Skullcap) for Cancer Patients -- 9.An Evidence-based Perspective of Hedyotis Diffusa or Oldenlandia Diffusa (Spreading Hedyotis) for Cancer Patients -- 10.An Evidence-based Perspective of Allium Sativum (Garlic) for Cancer Patients -- 11.An Evidence-based Perspective of Curcuma Longa (Turmeric) for Cancer Patients -- 12 -- An Evidence-based Perspective of Ganoderma Lucidum (Lucid Ganoderma) for Cancer Patients -- 13 -- An Evidence-based Perspective of Coriolus Versicolor (Multicolored Polypore Mushroom) for Cancer Patients -- 14 -- An Evidence-based Perspective of Lentinus Edodes (Shiitake Mushroom) for Cancer Patients -- 15 -- Molecular Targets of Resveratrol in Carcinogenesis -- 16 -- An Evidence-based Perspective of Camellia Sinensis (Green Tea) for Cancer Patients -- 17.Mylabris Phalerata (Chinese Blister Beetle) on Hematological Malignancies -- 18 -- An Evidence-based Perspective of Bufo Gargarizans (Asiatic Toad) for Cancer Patients -- 19 -- An Evidence-based Perspective of Herbal Remedies for Cancer Patients -- Index.
Keywords: Medicine; Cancer research; Complementary medicine; Acupuncture; Biomedicine; Cancer Research; Biomedicine general; Medicine/Public Health, general; Complementary & Alternative Medicine; Acupuncture; Electronic books